TASK SKILL APARATUR SIPIL NEGARA (STUDI KASUS PADA DINAS KEPENDUDUKAN DAN PENCATATATAN SIPIL KABUPATEN SAMPANG, JAWA TIMUR, INDONESIA) - Abdurahman; R.A Ratih Sonia Paradita; Dewi Casmiwati; Wildan Taufik Raharja (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
The state civil apparatus as the government administrator, service, and development is required to have adaptability in the 4.0 era, especially in organizing population administration service to explore the task skills of the state civil apparatus in the Department of Population and Civil Registration in Sampang, East Java, Indonesia. This study uses descriptive qualitative with interactive model data analysis techniques (Miles, Huberman, and Saldana, 2014: 8). Meanwhile, the theoretical study of task skills Fleishman, et al. (1991) include; knowledge dimension, the apparatus does not master the standard operating procedures that have been set by the Department of Population and Civil Registration; physical agility dimension, most of the apparatus only "know" how to operate a computer, and they are the expert; The interpersonal capacity dimension of the apparatus still does not have good interpersonal skill, as can be seen from public complaints regarding the attitude of the apparatus that is considered less friendly and communicative; Meanwhile, the dimension of intellectual ability level of creativity, innovation, problem solving in completing task demands are still not optimal, such as in manual services. They tend to apply the old pattern, so that the employee work target is not achieved